Capturing the multidimensionality of land-use agents in a deforestation hotspot - Faingerch, Melina (2025)
Given increasing recognition that strategies to transition to sustainable land use should be context specific, structuringthe diversity of land-use agents is important. This is particularly so for the world’s tropical deforestation frontiers, where rapid landusechange, driven by diverse agents, leads to stark social-ecological trade-offs. Focusing on the Argentinean Dry Chaco, a globaldeforestation hotspot, we employed archetyping to identify key types of land-use agents using data from a questionnaire survey coveringthree main dimensions: agents’ capital assets (what they have), agents’ activities and management (what they do), and agents’ personalcharacteristics (who they are). We identified five well-differentiated types of land-use agents: forest-dependent smallholders, semisubsistenceranchers, crop–livestock farmers, agribusiness farmers, and commercial ranchers. Characterizing these major agent typesyielded three main conceptual and methodological insights. First, we reveal considerable heterogeneity of land-use agents in theArgentine Dry Chaco, allowing us to move beyond the common yet oversimplified and dichotomic view of agribusinesses vs.smallholders. Second, the agent typology based on all three dimensions captured the diversity of agents much better than any onedimensionaltypology alone, demonstrating the value of richer descriptions of land-use agents. Third, all our agent types sharecharacteristics in some dimensions yet differ in others (e.g., forest-dependent smallholders and crop–livestock farmers were similar inwho they are, yet different in what they do), explaining how more simplistic agent descriptions arrive at oversimplified agent types.Overall, our work highlights how archetyping can structure complex human–environment phenomena, diverse land-use agents in ourcase, for guiding tailored, actor-specific policy interventions.